Evaluasi Pelatihan EVALUASI PELATIHAN TATA NASKAH DINAS SEBAGAI IMPLEMENTASI KEMENTERIAN KEUANGAN CORPORATE UNIVERSITY - Agus Suharsono (Jurnal Kewidyaiswaraan, 2021)
Ministry of Finance implemented Ministry of Finance Corporate University strategy in developing employee competencies because the direction of employee competency development in 2020-2024 RPJM is world class government, one of which is through the ASN Corporate University management unit. Learning in Ministry of Finance Corporate University strategy must linked and matched by applying 70-20-10 learning model. Therefore, this study will evaluate second batch of 2019 Official Manuscripts Training organized by Yogyakarta Financial Education and Training Center because urgency and role to realize this strategy. The evaluation method used Kirkpatrick level-1 and level-2 models. The results of the evaluation of the mean learning outcomes of the participants were 85.26 with a good predicate, evaluation of training implementation with a score of 92, the mean result of the teacher evaluation was 4.73 or very good. This training is carried out classically so that the scope of participants is limited and has not implemented the Ministry of Finance's Corporate University learning model 10-20-70. In addition, training has not been able to meet the applicable and impactful characteristics. For this reason, it is suggested to apply the 10-20-70 learning model in order to expand the scope of participants and support organizational performance.